Clinical evaluation of the potential drug–drug interactions of savolitinib: Interaction with rifampicin, itraconazole, famotidine or midazolam. Issue 2 (21st August 2021) - Ren, Song; Vishwanathan, Karthick; Cantarini, Mireille; Frewer, Paul; Hara, Indira; Scarfe, Graeme; Burke, Wendy; Schalkwijk, Stein; Li, Yan; Han, David; Goldwater, Ronald
Abstract : Aims: We investigated savolitinib pharmacokinetics (PK) when administered alone or in combination with rifampicin, itraconazole or famotidine, and investigated midazolam PK when administered with or without savolitinib in healthy males. Methods: Savolitinib PK was evaluated before/after: rifampicin (600 mg once daily [QD] for 5 days); itraconazole (200 mg QD for 5 days); a single dose of famotidine (40 mg QD) 2 hours before savolitinib. Midazolam PK was evaluated before/after midazolam (1 mg QD) with or without savolitinib (600 mg QD). Each study enrolled 20, 16, 16 and 14 volunteers, respectively. Plasma samples were collected to determine the effect on PK. Results: The geometric mean ratios (GMR, %) (90% confidence intervals [CIs]) for savolitinib alone and in combination for C max, AUC respectively, were 45.4 (41.4–49.9), 38.5 (34.2–43.3) in the rifampicin study ( n  = 18); 105.2 (87.7–126.3), 108.4 (96.3–122.1) in the itraconazole study ( n  = 16); and 78.8 (67.7–91.7), 87.4 (81.2–94.2) in the famotidine study ( n  = 16). The GMRs (90% CIs) for midazolam alone and in combination with savolitinib for C max, AUC respectively, were 84.1 (70.0–101.0), 96.7 (92.4–101.1) ( n  = 14). Savolitinib alone or in combination was well tolerated. Conclusions: Co‐dosing of rifampicin significantly reduced exposure to savolitinib vs savolitinib alone; co‐dosing of itraconazole or midazolam with savolitinib had no clinically significant effect on savolitinib or midazolam PK, respectively. Co‐dosing of famotidine with savolitinib reduced exposure to savolitinib, although this was not considered clinically meaningful. No new savolitinib‐related safety findings were observed.